Road safety audit: a case study on NH-65 - Bharat Kumar, Tummala; Jeswanth Chowdary, Chukkapalli (International Journal of Engineering and Technology, 2018)
In India there is road network of 33 lakh kilometres of which nearly 65% of the cargo activity and 80% of traveller movement is on the road networks. National Highways constitute around 1.7% of the road network but carry about 40% of the aggregate road traffic. Number of vehicles has been increasing at a normal pace of 10.16% for every annum in the course of the most recent five years. Road safety audit is the formal methodology for getting accident potential and safety potential in the development of new road schemes and the schemes for the improvement and maintenance of the existing road facilities. Accident prevention and accident reduction are the two main strategies in the road safety. In this case study we analyse the NH-65 which is the major highway connecting VIJAYAWADA and HYDERABAD from the 270thKM to 247th KM. The highway carries considerable amount of traffic throughout the day and it has number of conflict points such as villages, industries. Detailed analysis of NH-65 will be carried out from the point of view of safety and geometric design aspects will be performed. This paper aims to identify deficiencies, improving design aspects, enhancing credibility of the roads.Â Â
Keywords: Accident; improving design aspects; road safety.